(untitled) (Itinera, 2024)
The contribution aims to explore the theme of disgust within the rejected substrate of the monstrous. While there is a fascination with what we perceive as deformed – be it body, matter, or space – this fascination often struggles to mature into an approach that em- braces the monstrous as a design strategy. This research seeks to frame the disruptive potentials of the monstrous as generative for the broader culture of design, reintroducing value to concepts and practices of dislocation. Starting from an interpretation of the pri- mary monstrous, the mother (Braidotti, 1994), the study intends to offer an overview that spans visual arts and performative theories, relating this density to its spatial application potentials. Through the relationship between perception and imagination, the paper pro- poses openings towards the wild (Metta, 2021), suggesting spatialized methodologies of the monstrous as privileged practices of action in marginal urban contexts, such as the province. By examining cases that address the legitimacy of bodies and their transition, and forms of investigation linking the liminality of territory with that of the individual (Miguel Vila, Fiordilatte, 2021, Padovaland, 2020, Comfrotless 2023; HPO, Provinciale, 2023; basso profilo, CAMPOTTO: accordi di comunità verso un nuovo piano di stazione, 2023 ), the paper investigates the oscillation between rejection and imagination, theoriz- ing monstrous practices as fantastic opportunities to transcend the established spatial con- ditions. The selected works offer a means to consider the transformation of rejected hu- man and territorial bodies into non-institutionalized potential for regeneration. The article works on the ambivalence between the warning of the uncanny and the vision of the transformed contexts, the conception of a space of dissent and grafts. Such viscosities, despite their complexity, retain a potentially generative disorder, not to be suppressed but to be engaged in a discursively implicated practice with the unexpected, bringing human- ity closer to a concept of wild, ever-changing transformation.